Can we define success criteria for lumbar disc surgery?: Estimates for a substantial amount of improvement in core outcome measures. (1st January 2013) - Solberg, Tore; Johnsen, Lars Gunnar; Nygaard, Øystein P; Grotle, Margreth
Abstract : Background and purpose A successful outcome after lumbar discectomy indicates a substantial improvement. To use the cutoffs for minimal clinically important difference (MCID) as success criteria has a large potential bias, simply because it is difficult to classify patients who report that they are "moderately improved". We propose that the criteria for success should be defined by those who report that they are "completely recovered" or "much better". Methods A cohort of 692 patients were operated for lumbar disc herniation and followed for one year in the Norwegian Registry for Spine Surgery. The global perceived scale of change was used as an external criterion, and success was defined as those who reported that they were "completely recovered" or "much better". Criteria for success for each of (1) the Oswestry disability index (ODI; score range 0–100 where 0 = no disability), (2) the numerical pain scale (NRS; range 0–10 where 0 = no pain) for back and leg pain, and (3) the Euroqol (EQ-5D; –0.6 to 1 where 1 = perfect health) were estimated by defining the optimal cutoff point on receiver operating characteristic curves. Results The cutoff values for success for the mean change scores were 20 (ODI), 2.5 (NRS back), 3.5 (NRS leg), and 0.30 (EQ-5D). According to the cutoff estimates, the proportions of successful outcomes were 66% for the ODI and 67% for the NRS leg pain scale. Interpretation The sensitivity/specificity values for the ODI and leg pain were acceptable, whereas they were very low for the EQ-5D. The cutoffs for success can be used as benchmarks when comparing data from different surgical units.